Urgensi Pembatasan Masa Jabatan Anggota Legislatif dalam Upaya Pencegahan Penyalahgunaan Kekuasaan - Haryo Adhi Wijoyo; Sunny Ummul Firdaus (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This research analyzes the urgency of limiting the term of office of legislative members in an effort to prevent abuse of power. This research is a prescriptive normative legal research to analyze the urgency of limiting the term of office of legislative members and preventing abuse of power by legislators. This research uses primary legal materials in the form of statutory regulations and secondary legal materials in the form of legal books, legal journals and other literature. Data collection was carried out through library research. In writing this law, the author uses a statutory approach and a conceptual approach. The results of this study indicate that the laws and regulations in Indonesia do not explicitly regulate the limitation of the term of office of legislative members, and the urgency of limiting the term of office of legislative members is needed in order to avoid abuse of power and as a better regeneration of leaders.